Forecasting Vegetable Crop Production in Jambi Province Using Linear Trend Analysis - Hidayati, Rahmi; Arianti, Dwi; Iqamah Elza , Nurul (JALOW | Journal of Agribusiness and Local Wisdom, 2026)
This analysis is crucial given the strategic role of the horticulture sector in providing nutritious food and its potential contribution to the Free Nutritious Food Program (MBG). The approach used is descriptive quantitative with a linear trend analysis method. Secondary data on annual vegetable production were obtained from the Central Bureau of Statistics (BPS) of Jambi Province. The linear trend equation Yt = aXt + b was calculated using the least squares method to measure the average annual change in production (a) and the model's coefficient of determination (R²). The analysis results show that all 10 commodities recorded a positive average annual increase trend. Large Chili had the highest growth rate, averaging 15,098 tons per year. The model showed a strong fit for commodities such as Chinese Cabbage/Mustard Greens (R²=0.8225) and Spring Onions (R²=0.8237). However, significant fluctuations were identified in Cabbage (R²=0.4983) and Bird's Eye Chili (R²=0.4799), indicating a high influence of non-linear factors. A very sharp surge in production occurred in the last two years (2023–2024), especially for Bird's Eye Chili and Eggplant, which recorded the highest production. Based on the strong linear trend projections, vegetable production in Jambi Province is predicted to continue increasing and stabilize at a high level, with Large Chili projected to reach 213,294 tons by 2027. The implications of this research are the need for risk mitigation of volatility (especially for Cabbage and Bird's Eye Chili) and an increase in post-harvest and distribution infrastructure capacity to accommodate larger production volumes in the future.